2014
DOI: 10.11118/actaun200654020131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ewe's milk by FT Near Infrared spectroscopy: measurement of samples on Petri dishes in reflectance mode

Abstract: AbstractŠUSTOVá, K., KUCHTíK, j., KRáČMAR, S.: Analysis of ewe's milk by FT Near Infrared spectroscopy: measurement of samples on Petri dishes in reflectance mode. Acta univ. agric. et silvic. Mendel. Brun., 2006, LIV, No. 2, pp. 131-138 Our work deals with a possibility of determination of basic composition (dry matter, fat, protein, casein, lactose and urea nitrogen) of ewe's milk and colostrum by FT NIR spectroscopy. Samples of milk were warmed to 40 °C, agitated, cooled to 20 °C, transferred into Petri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Therefore, after the elimination of outliers, we observed a pattern of similarity between the values from the reference methods and those obtained with the instrumental methodologies for all parameters (Table 1; p>0.05). This fact is verified in other similar studies, for Fat% and Prot% (Aernouts et al, 2015;Šustová et al, 2007;Šustová et al, 2014) and SCC (Hanuš et al, 2009;Hanuš et al, 2014b;Krupa Rose et al, 2022).…”
Section: Resultssupporting
confidence: 79%
“…Therefore, after the elimination of outliers, we observed a pattern of similarity between the values from the reference methods and those obtained with the instrumental methodologies for all parameters (Table 1; p>0.05). This fact is verified in other similar studies, for Fat% and Prot% (Aernouts et al, 2015;Šustová et al, 2007;Šustová et al, 2014) and SCC (Hanuš et al, 2009;Hanuš et al, 2014b;Krupa Rose et al, 2022).…”
Section: Resultssupporting
confidence: 79%
“…Even though the DESIR method obtained poorer calibration statistics than the transflectance method, the accuracy of the former was fairly good; R 2 CV over 0.90 means an excellent capacity for quantitative analysis (Núñez-Sánchez et al 2002). Different authors had reported good R 2 CV for calibration equations for diverse constituents obtained for milk from different species: total casein, alphas, beta and kappa caseins from goat's milk (0·87, 0·86, 0·92 and 0·86, respectively; Díaz-Carrillo et al 1993); somatic cell count ( SCC ) from cow's milk (0·85, Tsenkova et al 2001); casein from cow's milk (0·96 to 0·98, Laporte & Paquin, 1999; 0·93, Šustová et al 2006). Particularly, Núñez-Sánchez et al (2002) compared the ability to predict milk constituents (casein, protein, fat, total solids and SCC) by NIRS with DESIR (reflectance) and with liquid samples (folded transmission) of ewe milk.…”
Section: Discussionmentioning
confidence: 99%
“…Stanovení těchto minoritních složek je důležité nejen v kontrole kvality mléka, ale zejména v kontrole zdravotního a výživového stavu dojnic (Famigli-Bergamini, 1987;Illek a Pechová, 1997). Pro určení mléčného složení (majoritní i minoritní složky) je v poslední době místy popisována a používána i metoda NIR-FT (Tsenkova et al, 2000;Kukačková, et al, 2000;Jankovská a Šustová, 2003;Kráčmar et al, 2004;Šustová et al, 2006.…”
unclassified